(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article examines the theoretical and methodological foundations of the organization and planning of the audit of financial results. Modern approaches, audit planning and its stages are analyzed in order to improve the efficiency of the audit of financial results. As a result, important recommendations for the organization and planning of the audit process were developed.